Problematika Keterlambatan Penyampaian Tanggapan SP2DK Wajib Pajak yang di terbitkan oleh KPP Pratama di kota Pontianak - Aswat, Ibnu (Jurnal Buana Akuntansi, 2024)
SP2DK is a letter from the Tax Office Director (KPP) issued to taxpayers to explain data and/or information regarding the suspected non-fulfillment of tax obligations in accordance with the provisions of tax legislation. The term SP2DK, commonly referred to as the "love letter" by the community, is considered a precursor to future trials and carries a worrying nuance. However, if interpreted correctly, SP2DK is a control mechanism and follow-up in the Indonesian tax self-assessment system, which provides taxpayers with the opportunity to review and clarify their tax obligations. Regarding the self-assessment tax system in Indonesia, the monitoring process must continue to ensure tax compliance. Thus, tax collection activities can be carried out according to applicable regulations. The Pratama Tax Office gives taxpayers a deadline of 14 days (from the date of dispatch) to respond to the SP2DK. According to the 2021 Annual Report data from the Directorate General of Taxes (DJP), SP2DK production last year amounted to 3.73 million letters. This number increased by approximately 53.86% compared to the production in 2020 of 2.42 million letters.